The Effects of Star Fruit (Averrhoa carambola Linn.) Extract on Body Mass Index, Fasting Blood Glucose, and Triglyceride Levels in Male Rats with Obesity and Type 2 Diabetes Mellitus - Sari, Yustika; Indarto, Dono; Wasita, Brian (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Obesity is the main risk factor of diabetes by which induces insulin resistance. Epicatechin gallate can virtually interact with sodium-glucose co-transporter 2 as same as dapagliflozin and is found in green tea and star fruits. AIM: This study aimed to investigate the effects of methanol extract of star fruit (MES) on body weight (BW), body mass index (BMI), fasting blood glucose (FBG), and triglyceride levels in male rats with obesity and type 2 diabetes mellitus (T2DM). METHODS: Twenty-four male Sprague-Dawley rats were randomly assigned to normal and high-fat diet (HFD) groups. Obesity was induced with a HFD diet for 5 weeks and followed by induction of T2DM with 230 mg/kg BW nicotinamide and 65 mg/kg BW streptozotocin injections. Twenty-one obesity and T2DM rats were randomly assigned to negative control (n = 3) and the remaining rats in the MES1-3 groups, which were given 250, 500, and 1000 mg/kg BW/day MES. Data of BW, BMI, FBG, and triglyceride levels were collected at day 1, 14, and 28 interventions. Data were statistically analyzed using parametric and non-parametric tests with p < 0.05 considered significant. RESULTS: The MES3 group (282.56 ± 10.75 g) had significantly lower mean BW than the MES2 group (331.33 ± 13.17 g, p = 0.035). The duration of MES administration significantly decreased BW (p = 0.009) and BMI (p = 0.034) compared with the negative control. The mean triglyceride levels in MES1 (93.72 ± 53.69 mg/dl, p = 0.020), MES2 (71.98 ± 35.72 mg/dl, p = 0.025), and MES3 (56.68 ± 16.37 mg/dl, p = 0.020) groups significantly lower than the control group (1042.13 ± 681.74 mg/dl) on day 14. The mean FBG levels in MES1 (437.85 ± 33.04 mg/dl) and MES2 (353 ± 33.04 mg/dl) groups were also lower than the control group (470.97 ± 33.04 mg/dl). CONCLUSION: Administrations of 250, 500, and 1000 mg/kg BW/day MES decrease BW, BMI, and triglyceride level but increase FBG level in male rats with obesity and T2DM for 14 and 28 days.